Method of incident low-energy gamma-ray direction reconstruction in the GAMMA-400 gamma-ray space telescope. Issue 3 (January 2016) - Kheymits, M D; Leonov, A A; Zverev, V G; Galper, A M; Arkhangelskaya, I V; Arkhangelskiy, A I; Suchkov, S I; Topchiev, N P; Yurkin, Yu T; Bakaldin, A V; Dalkarov, O D
Abstract: The GAMMA-400 gamma-ray space-based telescope has as its main goals to measure cosmic γ-ray fluxes and the electron-positron cosmic-ray component produced, theoretically, in dark-matter-particles decay or annihilation processes, to search for discrete γ-ray sources and study them in detail, to examine the energy spectra of diffuse γ-rays — both galactic and extragalactic — and to study gamma-ray bursts (GRBs) and γ-rays from the active Sun. Scientific goals of GAMMA-400 telescope require fine angular resolution. The telescope is of a pair-production type. In the converter-tracker, the incident gamma-ray photon converts into electron-positron pair in the tungsten layer and then the tracks are detected by silicon- strip position-sensitive detectors. Multiple scattering processes become a significant obstacle in the incident-gamma direction reconstruction for energies below several gigaelectronvolts. The method of utilising this process to improve the resolution is proposed in the presented work.